The complexity of community participation: Professional perspectives on the definition and inclusion of community. Issue 4 (8th August 2022) - Garcia, Martha Lucia; Mizrahi, Terry; Korazim-Kőrösy, Yossi
ABSTRACT: This paper compares the perspectives of six professions -social workers, lawyers, nurses, physicians, psychologists and public health professionals- on ways to improve the health and social conditions of a prototypical low-income urban community. It examines how the cohort defined and deliberated on the process of involving "the community" in addressing issues facing a hypothetical neighborhood, even when the question was not part of the research guidelines. A framework for constituency participation emerged from the data and was further developed to include 5 components: "who, why, when, ways and what level." The type, level, and meaning of community was complex and multi-faceted, raising critical questions about professional-community relationships and the role of community development practitioners. Ultimately, community participation was identified as both difficult and transformative at the same time. Attention by community practitioners to the "five Ws framework for constituency participation" may maximize positive outcomes for collaboration between professionals and community.